La responsabilidad precontractual de la administración, el principio de buena fe y el deber de información a postores - Morón Urbina, Juan Carlos (Revista de Derecho, 2019)
The present Essay analyzes the duty of the Administration to provide reliable, complete and truthful information to the bidders whom it calls to participate in a selection process and also the consequences derived from the breach of this duty. In the same way, this Essay analyzes the scope of the duty to be informed that the bidders have when applying for selection processes called by the public entities.